Pengaruh Pendekatan TaRL Terhadap Kemampuan Membaca Siswa Kelas IV SDN 03 Kalijaga - Lestari, Linda Ulnia; Siregar, Deni; Hamdi, Zulfadli (Program Studi Pendidikan Masyarakat, 2026)
Abstract: This study aims to determine the effect of the Teaching at the Right Level (TaRL) approach on the reading ability of fourth-grade students. The researcher used a quantitative experimental research method. The design used was a one-group pretest-posttest design. The study population was all 127 students at SDN 03 Kalijaga. The sample size was 20 fourth-grade students. Data collection was conducted using tests. Data analysis in this study used normality tests, hypothesis testing, and normality tests using Liliefors. The results of the analysis of students' pretest scores obtained an l-count of 0.168 with an l-table value of 0.190, indicating that l-count < l-table. Meanwhile, the posttest normality test results obtained a calculated value of 0.163 with an ltable value of 0.190, indicating that the pretest and posttest data were normally distributed. Furthermore, the hypothesis test data analysis, based on the hypothesis test calculations using a paired sample t-test on 20 students, yielded a mean difference of 24, a standard deviation of 11.073, and a calculated t of 9.692 with a ttable of 2.093, with a significance level of 0.05. Therefore, the hypothesis